Boarding School Care System Based On Guidance And Counseling In Developing Intellectual Independence - Wildan Mahmudin; Ajid Thohir; Dudy Imanuddin Effendi; Abdul Rozak (International Journal of Science Education and Technology Management, 2026)
Developing intellectual independence by enhancing higher-order thinking skills in Islamic boarding schools often faces various obstacles. Many students struggle to develop critical and independent thinking skills, either due to environmental factors, inadequate teaching methods, or a lack of attention to their psychological development. As Islamic educational institutions, Islamic boarding schools play a crucial role in shaping the character and personality of their students. In addition to providing in-depth religious education, they also serve as a place for mental, spiritual, and social development. Within this development process, developing intellectual independence through higher-order thinking skills is crucial. This study aims to describe and analyze the guidance and counseling-based care system employed in Islamic boarding schools to develop intellectual independence at Riyadul Ulum Wadda'wah Condong Islamic Boarding School and Al Amin Islamic Boarding School in Tasikmalaya City. The approach used in this study is a qualitative one. A case study method was used. The results of the study indicate that a guidance and counseling-based care system significantly contributes to the development of guidance and counseling (BK) services in fostering the intellectual independence of students. Through this service, students are trained to think analytically, evaluatively, and creatively in dealing with academic and daily life problems.